The Influence of Total Quality Management, Leadership Style, Organizational Culture and Organizational Commitment on Employee Performance at PT. Tunas Mobilindo Perkasa Bandung - Yulia Dyah Anggraeni; Gurawan Dayona Ismail; Mochammad Mukti Ali; Nunung Ayu Sofiaty; Yoyo Sudaryo (Green Publisher Indonesia, 2025)
This research seeks to examine how “Total Quality Management (TQM), leadership style, organizational culture, and organizational commitment” on employee performance at PT. Tunas Mobilindo Perkasa Bandung. This research utilizes a quantitative research approach to examine causal relationships between variables. Multiple linear regression analysis was employed to analyze the data. The results indicate that all independent variables significantly affect employee performance both partially and simultaneously. In the partial model, TQM (β = 0.602, p < 0.005), leadership style (β = 0.826, p < 0.005), organizational culture (β = 0.801, p < 0.005), and organizational commitment (β = 1.000, p < 0.005) are all significant predictors of the outcome variable. Simultaneously, the four variables explain 95.1% of the variation in employee performance with an F value of 1778.807 and a significance of 0.000. Organizational commitment emerges as the most dominant factor, followed by organizational culture, leadership style, and TQM. These findings underline the importance of optimizing these four factors to enhance employee performance and support corporate goals.